Making friends just like us: child's play - Stockham, Jess (child's play Sydney, 2008)
"Making Friends Just Like Us" likely focuses on the importance of friendship and connection among individuals who share similar experiences or interests. It might explore themes of inclusivity, understanding, and the joy of forming bonds through shared activities or backgrounds. The narrative could showcase how friendships enrich our lives and the ways we can support one another in a diverse community.